Implementasi Nilai Toleransi Dan Cinta Tanah Air Pada Kelompok Kesenian Tari Lengger Krido Budoyo(Studi Kasus di Kelompok Kesenian Krido Budoyo Desa Krakal Dawung, Kecamatan Kertek, Kabupaten Wonosobo) - Wibowo, Bayu Prasetyo, Dra. Sundari, SH., M.Hum (2016)
This study aims to describe the implementation of the value of tolerance in the arts groups Tari Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, describes the implementation of patriotism in art groups Tari Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo 2015, describes the obstacles that hinder the implementation of the value of tolerance in the arts groups Tari Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, describes the obstacles that hinder the implementation of patriotism in art groups Tari Lengger Krido Budoyo Village Krakal Dawung, Subdistrict Kertek, Wonosobo regency in 2015, describes a solution to overcome obstacles in the implementation of the value of tolerance in the arts groups Tari Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, describes a solution to overcome obstacles in the implementation of patriotism in art groups Tari Lengger Krido Budoyo in the village of Krakal Dawung Sub Kertek, Wonosobo regency in 2015. This research is a qualitative descriptive study. Subjects in this study were community leaders and villagers in the village of Krakal Dawung, District Kertek, Wonosobo. The object of research is the implementation of the values of tolerance and love of the homeland in the arts Dance group Lengger Krido Krakal Dawung Budoyo Village, District Kertek, Wonosobo. Data collection techniques in this study is an interactive that includes interviews, observation, and documentation. This study uses two kinds of triangulation, the first triangulation of data sources in the form of information from places, events and documents containing records relating to the intended data. Second, triangulation techniques or methods of collecting data derived from interviews, observations, and documents. The results of this study can be concluded that: 1) Implementation of Value Tolerance Group of Art Dance Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, namely: a) Wants to cooperate with others despite differences in religion, b) Respect between religious communities, c) Maintain harmony in daily activities. 2) Implementation of patriotism in art groups Tari Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, namely: a) Using Indonesian language is good and true, b) Liking culture of the archipelago, c) Liked made in Indonesia. 3) Constraints Hinder Implementation of Value Tolerance Group of Art Dance Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, namely: a) Limiting interaction, b) Attitude fanatical adherents to the religion of their own, c) Disruption of harmony in daily activities / lack of own tolerance to others. 4) Constraints that impede implementation of patriotism in art groups Tari Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, namely a) The existence of several youths slang, b) Influenced by the western culture that considers cultural dances the past is considered to be old-fashioned, c) Tempted by the products from abroad, for example necklace. 5) The solution to overcome obstacles in the implementation of the value of tolerance in the arts groups Tari Lengger Krido Budoyo Village Krakal Dawung, District Kertek, Wonosobo regency in 2015, namely: a) advise to the individual to want to reduce the nature of bigotry against religion, b) is to be reduced bigotry towards religious nature, c) is more sensitive and has tepo sliro towards others. 6) The solution to overcome obstacles in the implementation of patriotism in the arts Dance group Lengger Krido Krakal Dawung Budoyo Village, District Kertek, Wonosobo regency in 2015, namely: a) required to learn to get used to practicing in the Indonesian language is good and true, b) explain to more love in their own cultural heritage, c) Stronghold Call to love the product itself.